AN ANALYSIS OF INTERJECTION IN WHATSAPP GROUP - Fatimah Azzahro; Joko Wibowo (English Language Teaching Journal, 2023)
This research aims to analyze the types and the meaning of interjection in the WhatsApp group. The research employs descriptive qualitative approach pragmatic since this research is conversation analysis the data were collected from the dialog or conversation student in WhatsApp group. The result of the research that The types of interjection that found in this group namely, the interjection of wonder, interjection of gratitude, interjection of hope, interjection of  invitation, interjection of surprise, interjection of admiration or satisfaction and interjection of annoyance.  The most frequently found part of interjection of wonder. There are three word of interjection wonder namely, haduh, loh kok bisa and leh. There are several meanings of interjection found by researchers, namely, the meaning of sadness, the meaning of wonder, the meaning of annoyance, the meaning of hope, the meaning of surprise, the meaning of invitation, the meaning of gratitude and the meaning of admiration.  Keywords: pragmatics, types and meanings of interjection, whatsapp group.